An efficient task matching schema with signature oriented encryption technique - Arijita Bhowmik; Somen Debnath; Parijata Majumdar; R. Chawngsangpuii (Utilitas Mathematica, 2025)
Crowdsourcing platforms have transformed task outsourcing by enabling large- scale human collaboration over the internet. A key factor in their success is the efficient matching of workers to tasks based on individual skills and preferences. However, this process often involves sharing sensitive personal data, raising seri- ous concerns about privacy and security. Existing solutions, such as traditional encryption and proxy re-encryption, struggle to balance scalability with strong privacy guarantees. In this paper, we propose a privacy-preserving task-matching framework that utilizes ring verification signatures to safeguard user anonymity and ensure data integrity. Unlike conventional methods, our approach removes the dependency on proxy re-encryption and effectively mitigates risks related to identity inference. We detail the system’s design, implementation, and security analysis, demonstrating its practical effectiveness in preserving privacy within dynamic and large-scale crowdsourcing environments.